2014
DOI: 10.1021/bi5004074
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Flexible Loop in 1-Deoxy-d-xylulose-5-phosphate Reductoisomerase Boosts Enthalpy-Driven Inhibition by Fosmidomycin

Abstract: 1-Deoxy-d-xylulose-5-phosphate reductoisomerase (DXR), which catalyzes the first committed step in the 2-C-methyl-d-erythritol 4-phosphate pathway of isoprenoid biosynthesis used by Mycobacterium tuberculosis and other infectious microorganisms, is absent in humans and therefore an attractive drug target. Fosmidomycin is a nanomolar inhibitor of DXR, but despite great efforts, few analogues with comparable potency have been developed. DXR contains a strictly conserved residue, Trp203, within a flexible loop th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Comparison of the S. schleiferi DXR apoenzyme and FSM complex structures reveals how the C-terminal capping region (α9-α11 and α16-18) shift position to allow for the α10-α11 loop to position Trp196 adjacent to the inhibitor (Fig 3D). Movement of this flexible loop is a key feature for FSM inhibition of DXR from a variety of microorganisms(38). The residues that interact with FSM in the S. schleiferi DXR are conserved in the crystal structures of DXR from E. coli, P. falciparum , and M. tuberculosis with some variation in the sequence of the α10-α11 loop, although the tryptophan that contacts FSM is conserved in all these enzymes(34,36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the S. schleiferi DXR apoenzyme and FSM complex structures reveals how the C-terminal capping region (α9-α11 and α16-18) shift position to allow for the α10-α11 loop to position Trp196 adjacent to the inhibitor (Fig 3D). Movement of this flexible loop is a key feature for FSM inhibition of DXR from a variety of microorganisms(38). The residues that interact with FSM in the S. schleiferi DXR are conserved in the crystal structures of DXR from E. coli, P. falciparum , and M. tuberculosis with some variation in the sequence of the α10-α11 loop, although the tryptophan that contacts FSM is conserved in all these enzymes(34,36,37).…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20] Murkin and co-workersd emonstrated ac hange in the rate-limiting step of the Mycobacterium tuberculosis Dxr-catalyzed reaction upon alterationo fT rp203 in the flap, thereby establishing af unctional link between this amino acid and chemical barrier crossing. [21] Inhibition andb inding studies with fosmidomycin confirmed the importance of the flap, andt he conserved tryptophan in particular, for ligand binding. Structural evaluation of as eries of Dxr-bound compounds including 3 and 4 ( Figure 2) showed that the indole group of Trp211i nt he Escherichia coli enzyme (EcDxr) is displaced in order to accommodate the inhibitors' pyridine/quinoline rings, which form p-p stacking or chargetransfer interactions with the indole of the tryptophan side chain.…”
Section: Introductionmentioning
confidence: 90%
“…This flap is considered essential for the catalytic activity of Dxr . Murkin and co‐workers demonstrated a change in the rate‐limiting step of the Mycobacterium tuberculosis Dxr‐catalyzed reaction upon alteration of Trp203 in the flap, thereby establishing a functional link between this amino acid and chemical barrier crossing . Inhibition and binding studies with fosmidomycin confirmed the importance of the flap, and the conserved tryptophan in particular, for ligand binding.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, W203F and W203Y exhibited greatly diminished burst kinetics and larger primary 2 H KIEs on k cat than the wild-type enzyme (recall Section 3.2), indicating that mutation had rendered chemical steps more rate limiting. Surprisingly, fosmidomycin was found to bind more tightly to these mutants by up to an order of magnitude, a result that was attributable to a large increase in binding enthalpy [110].…”
Section: Flexible Loopmentioning
confidence: 96%
“…Attempts to substitute this tryptophan with non-aromatic amino acids (Leu, Val or Ala) led to the mutants strongly impaired in both binding and catalytic properties [109]. Similarly, Kholodar and co-workers [110] demonstrated a lack of activity for W203G and W203A mutants of M. tuberculosis DXR. Interestingly, however, phenylalanine and tyrosine substitutions were well accommodated (Table 4), underscoring the necessity for an aromatic residue.…”
Section: Flexible Loopmentioning
confidence: 97%